2005
DOI: 10.1073/pnas.0409454102
|View full text |Cite
|
Sign up to set email alerts
|

Host population persistence in the face of introduced vector-borne diseases: Hawaii amakihi and avian malaria

Abstract: The past quarter century has seen an unprecedented increase in the number of new and emerging infectious diseases throughout the world, with serious implications for human and wildlife populations. We examined host persistence in the face of introduced vector-borne diseases in Hawaii, where introduced avian malaria and introduced vectors have had a negative impact on most populations of Hawaiian forest birds for nearly a century. We studied birds, parasites, and vectors in nine study areas from 0 to 1,800 m on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
189
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 194 publications
(208 citation statements)
references
References 34 publications
(45 reference statements)
6
189
0
2
Order By: Relevance
“…In this case, such habitat is associated with rock holes along stream margins. In support of this hypothesis and in contrast to other areas in Hawai'i where malarial prevalence is higher (Atkinson et al, 2005), we found no significant interaction between elevation and host status (native or nonnative species) and no significant association between elevation and malarial infection. Our sampling was conducted during an abnormally dry fall, and during this 5-mo study, we experienced only one episode of torrential rain with flash flooding that would have scoured stream margins.…”
Section: Larval Surveyssupporting
confidence: 70%
See 4 more Smart Citations
“…In this case, such habitat is associated with rock holes along stream margins. In support of this hypothesis and in contrast to other areas in Hawai'i where malarial prevalence is higher (Atkinson et al, 2005), we found no significant interaction between elevation and host status (native or nonnative species) and no significant association between elevation and malarial infection. Our sampling was conducted during an abnormally dry fall, and during this 5-mo study, we experienced only one episode of torrential rain with flash flooding that would have scoured stream margins.…”
Section: Larval Surveyssupporting
confidence: 70%
“…We found a low prevalence of both poxlike lesions and malarial infections in Kīpahulu Valley relative to other locations in Hawai'i where comparable methodologies have been used (Atkinson et al, 2005). This suggests that these two introduced diseases are not well established in this area.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations